Quantification of rumen undegradable protein fractions of conventional and non conventional protein supplements by SDS-PAGE - Wadhwa, M; Kaur, N; Bakshi, M P S (The Indian Journal of Animal Sciences, 2012)
Conventional [solvent extracted GNC and mechanically extracted mustard cake (MC)], and non-conventional protein supplements [machanically extracted castor oilseed cake (COSC), un-decorticated solvent extracted neem seed cake (NSC) and corn gluten meal (CGM)] before and after rumen incubations for different intervals were subjected to sequential fractionation into globulin, albumin, prolamin and glutelins on the basis of solubility. The polypeptides in globulin, prolamin and glutelin fraction of groundnut cake with molecular weight 35, 15, 16 and 19 KDA, respectively, were highly resistant to microbial degradation even after 24h or rumen incubation. The degradation pattern of mustard cake revealed that subunits of globulin, prolamin and glutelins with MW of 14–33, 14 and 31 KDA, respectively, were highly resistant to microbial degradation. In NSC subunits with MW 124 (in globulin), 30 (in albumin), 66 (in prolamin) and 54 kDa (in glutelin) were resistant to microbial degradation. The subunits in prolamin fraction of CGM with MW 18, 24 and 43 kDa and that in glutelin fraction with MW of 22 and 60 kDa were found to be highly resistant to microbial degradation. The results conclusively revealed that in majority of the cases, the low molecular weight polypeptides in the tested protein supplements showed resistance to rumen microbial fermentation, even after 48h of rumen incubation.